2019
DOI: 10.1002/adbi.201800318
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Handling and Analysis of Giant Vesicles for Use as Artificial Cells: A Review

Abstract: One of the goals of synthetic biology is the bottom‐up construction of an artificial cell, the successful realization of which could shed light on how cellular life emerged and could also be a useful tool for studying the function of modern cells. Using liposomes as biomimetic containers is particularly promising because lipid membranes are biocompatible and much of the required machinery can be reconstituted within them. Giant lipid vesicles have been used extensively in other fields such as biophysics and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 107 publications
(219 reference statements)
2
40
0
Order By: Relevance
“…[126] Recently, microsized vesicles (mainly giant unilamellar vesicles) have surged to a new role as ideal models of artificial cells and cell membrane. [132] The advantages derived from the use of microfluidics technique for their production reside mainly in the degree of control achievable on size, lamellarity, membrane composition, and payload. [131,133,134] At the same time it is possible to produce high number of such vesicles, reducing the overall costs.…”
Section: Microvesicles: From Polymerosomes To Artificial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[126] Recently, microsized vesicles (mainly giant unilamellar vesicles) have surged to a new role as ideal models of artificial cells and cell membrane. [132] The advantages derived from the use of microfluidics technique for their production reside mainly in the degree of control achievable on size, lamellarity, membrane composition, and payload. [131,133,134] At the same time it is possible to produce high number of such vesicles, reducing the overall costs.…”
Section: Microvesicles: From Polymerosomes To Artificial Cellsmentioning
confidence: 99%
“…[137] Interestingly, by mechanical compressing the giant unilamellar vesicles, Robinson et al observed a spontaneous rearrangement of the lipid domains culminating into a the formation of bigger domains. [132] Artificial cells and artificial cell membranes help in the breaking down of the complex cellular machine, one mechanism at the time to better understand their function. [133,138] However, the complexity of the cellular environment has proven difficult to recreate either in terms of membrane features (as discussed above) or in terms of intracellular organelles complexity.…”
Section: Microvesicles: From Polymerosomes To Artificial Cellsmentioning
confidence: 99%
“…GUVs are considered the gold standard of cellular mimics owing to their similarity in size to that of a mammalian cell. Moreover, with advances in technologies, such as microfluidics for their production and handling, GUVs are looking like an increasingly more attractive option.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it will be interesting to observe how multiple vesicle systems respond to external factors: not only compression, as shown here on single artificial cells, but with osmotic gradients, changes in heat, and also applied shear stresses. We are therefore developing systems to model proto‐tissues by using high‐capacity microfluidic vesicle capture with this future goal in mind …”
Section: Resultsmentioning
confidence: 99%